Korelasi Antara People Pleasing dengan Attachment Pada Siswa SMA Negeri 12 Banjarmasin - Hayati, Sri Ayatina; Haryadi, Rudi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Teenagers often think about the possibilities that could happen. They think about ideal characteristics of themselves, others, and the world. We often encounter individuals with pleasant attitudes in life. However, sometimes, they don't realize they have symptoms of a people-pleasing attitude. Attachment does not always have a good impact on a person, especially when the individual enters the world of adolescence. This research analyzes the relationship between People-Pleasure and Attachment of SMA Negeri 12 Banjarmasin students. The research design used is correlational research of two variables: variable (X) People Pleasing and variable (Y) Attachment. The sample was taken using random sampling from 62 students. The scale used in this research is People Pleasing by Braiker (2001), which consists of 24 items, and the Attachment Scale (Inventory of Parent and Peer Attachment/IPPA) by Armsden & Mark T. Greenberg in 1987, which consists of 25 items. Validity in this research is in the form of Pearson Correlation people pleaser validity 0,63 and Attachment 0,58, and reliability in this research is Cronbach's Alpha with people pleaser reliability 0.722 and Attachment 0.703. The hypothesis test results show a very strong and significant correlation between the people-pleasing and Attachment variables of 0.944.